2020
DOI: 10.3389/fphys.2020.566584
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Suppresses IL-6/STAT3 Signaling and Promotes Cytokine Secretion in Cultured Skeletal Muscle Cells

Abstract: Pirkmajer et al. Ouabain Modulates Myocyte IL-6/STAT3 Signaling might represent a negative feedback in the IL-6/STAT3 pathway. Collectively, our results implicate a role for CTS and NKA in regulation of the IL-6 signaling and secretion in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 145 publications
(240 reference statements)
3
27
0
Order By: Relevance
“…As assessed by mRNA measurements, human skeletal muscle expresses primarily NKAα2 (~87% of NKAα transcripts) and NKAα1 (~13% of NKAα transcripts) [23], consistent with data from rat muscles, which indicated that NKAα2 represents~60-90% of NKAα subunits [12,[70][71][72][73]. NKAα2 was robustly expressed in differentiated CD56 + myotubes (~48% of NKAα transcripts), but NKAα1 remained the predominant NKAα isoform (>50% of NKAα transcripts) in cells from most donors (Fig 8), consistent with observations in our recent study [24]. Innervation or EPS did not further increase NKAα2 mRNA, indicating neither formation of functional neuromuscular junctions nor contractions are essential for regulation of NKAα2 expression.…”
Section: Plos Onesupporting
confidence: 81%
See 2 more Smart Citations
“…As assessed by mRNA measurements, human skeletal muscle expresses primarily NKAα2 (~87% of NKAα transcripts) and NKAα1 (~13% of NKAα transcripts) [23], consistent with data from rat muscles, which indicated that NKAα2 represents~60-90% of NKAα subunits [12,[70][71][72][73]. NKAα2 was robustly expressed in differentiated CD56 + myotubes (~48% of NKAα transcripts), but NKAα1 remained the predominant NKAα isoform (>50% of NKAα transcripts) in cells from most donors (Fig 8), consistent with observations in our recent study [24]. Innervation or EPS did not further increase NKAα2 mRNA, indicating neither formation of functional neuromuscular junctions nor contractions are essential for regulation of NKAα2 expression.…”
Section: Plos Onesupporting
confidence: 81%
“…Primary human skeletal muscle cells for differentiation and co-culture (innervation) experiments were prepared from samples of the semitendinosus muscles, which were obtained during routine orthopaedic surgery as surgical waste, and cultured as described [24,30,32]. All donors of skeletal muscle tissue required surgery for medical reasons and no tissue was removed solely for the purpose of research.…”
Section: Culturing and Differentiation Of Human Skeletal Muscle Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, although ouabain is proposed to be a specific inhibitor of the Na,K-ATPase, its ability to activate the Na,K-ATPase at concentrations comparable to its endogenous level [ 33 , 34 , 35 ] and thus, to hyperpolarize the sarcolemma [ 36 ] was also shown. While the ability of nanomolar ouabain to activate intracellular signaling in cultured human skeletal muscle cells is well-documented [ 37 , 48 ], little is known about its role in the regulation of skeletal muscle function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, at subnanomolar concentrations that correspond to the level of circulating endogenous analog, ouabain is shown to activate the Na,K-ATPase [ 33 , 34 , 35 ] and to hyperpolarize the sarcolemma [ 36 ]. Moreover, it has been shown that nanomolar concentrations of ouabain modulate interleikin-6 (IL-6) secretion and IL-6/STAT3 signaling pathways [ 37 ].…”
Section: Introductionmentioning
confidence: 99%